2019
DOI: 10.35940/ijeat.f9323.109119
|View full text |Cite
|
Sign up to set email alerts
|

Bamboo Concrete Bond Strength

Abstract: Bamboo reinforced concrete is expected to be an alternative to steel reinforced concrete as a building material. Steel, when used for construction activities, is energy intensive and causes pollution. In this context, the use of bamboo, which is a fast growing, affordable and ecologically friendly solution; especially in a tropical country like India, is being considered as a suitable material for structural applications. It is potentially superior to steel in terms of its weight to strength ratio. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…The failure modes of all cylinders except for the reference or with brine wastewaters and for different diameters of reinforcement steel were similar (Figures 6-c and 9). The cracks were gradually observed and widened along with the distance of the steel rod inside the sample, which is (20 cm) until the sample failed or collapsed permanently, which is in line with such testing, clarification of the EC2-2004, RILEM -CEB RC6 (1983), and many researchers [26][27][28][29][30]. Experiments have indicated that the durability really decreases at a lower bond.…”
Section: Reinforcement-concrete Bond With Brine Wastewaterssupporting
confidence: 70%
See 1 more Smart Citation
“…The failure modes of all cylinders except for the reference or with brine wastewaters and for different diameters of reinforcement steel were similar (Figures 6-c and 9). The cracks were gradually observed and widened along with the distance of the steel rod inside the sample, which is (20 cm) until the sample failed or collapsed permanently, which is in line with such testing, clarification of the EC2-2004, RILEM -CEB RC6 (1983), and many researchers [26][27][28][29][30]. Experiments have indicated that the durability really decreases at a lower bond.…”
Section: Reinforcement-concrete Bond With Brine Wastewaterssupporting
confidence: 70%
“…The specimens are cylinders measuring 150×300 cm of concrete, and a steel bar was poured into the center of the sample and tested according to the ASTM C900 -19. Samples with ratios of more than 15% were not used, and this is due to previous studies [29][30][31][32], which proved that the use of ratios greater than 15% leads to weak strength concrete on compression and bending.…”
Section: Introductionmentioning
confidence: 99%
“…Current Advances in Materials Applications II Vijay Wairagade et al, 2019 [22] carried out a rebound hammer test with the target of predicting on the mechanical properties of the concrete columns used in the college. A number of column specimens had been tested in order to correlate the in-site concrete strengths resulted from rebound hammer method with the cubical strength resulted from the destructive method.…”
mentioning
confidence: 99%